Income inequality and economic growth: An empirical investigation in South Africa - Kholeka Mdingi; Sin-yu Ho (Cogent Economics & Finance, 2023)
This study examines the relationship between income inequality and economic growth in South Africa for the period 1989 to 2018. The study is motivated by the high disparity in income inequality and stagnant economic growth that South Africa is experiencing. Using the autoregressive distributed lag (ARDL) bounds testing technique, we established a long-run relationship between economic growth and income inequality. The results revealed that income inequality has a negative impact on economic growth in the long run, and no effect in the short run. These results are robust with an estimation of the ARDL procedure that considers structural breaks. Therefore, policymakers should employ strategies that entail a double effect of growth in national income and consider the distribution of income in the long run. These policies include human capital accumulation, easily accessible education, and reduction in labour market dualism.
Keywords: C22; D63; O15; 330; ARDL bounds test; economic growth; Income inequality; South Africa